Theory Beyond Structure and Agency Introducing the Metric/Nonmetric Distinction - Guy, Jean-Sébastien (Palgrave Studies in Relational Sociology,, 2019)
"In this insightful and highly readable book, Jean-Sébastien Guy takes us on an intellectual tour de force that makes us see the social world in a different light. A fresh perspective and an essential contribution to the current discussions of social systems and relational sociology." -Jan A. Fuhse, Heisenberg Fellow at the Institute of Social Sciences, Humboldt University of Berlin, Germany "In this original and provocative book, Jean-Sebastien Guy convincingly shows how the problem of structure and agency that has preoccupied sociologists throughout the history of their discipline amounts to an optical illusion. Employing the concepts of the metric and the nonmetric and using a variety of readily accessible examples, the author proposes an entirely different social theoretical lens that is perceptive to the internal variety of social reality." -Olli Pyyhtinen, Professor of Sociology at the University of Tampere, Finland This book offers asolution for the problem of structure and agency in sociological theory by developing a new pair of fundamental concepts: metric and nonmetric. Nonmetric forms, arising in a crowd made out of innumerable individuals, correspond to social groups that divide the many individuals in the crowd into insiders and outsiders. Metric forms correspond to congested zones like traffic jams on a highway: individuals are constantly entering and leaving these zones so that they continue to exist, even though the individuals passing through them change. Building from these concepts, we can understand "agency" as a requirement for group identity and group membership, thus associating it with nonmetric forms, and "structure" as a building-up effect following the accumulation of metric forms. This reveals the contradiction between structure and agency to be a case of forced perspective, leaving us victim to an optical illusion.